Implementasi Kebijakan Otonomi Khusus di Aceh [Implementation of Special Autonomy Policies In Aceh] - Debora Sanur (Sekretariat Jenderal DPR RI, 2020)
The granting of special autonomy or special authority by the central government to the Province of Aceh through the concept of asymmetric decentralization was aimed at embracing the province of Aceh to remain within the territory of the Republic of Indonesia and improve the welfare of the people of Aceh. Nevertheless, in its implementation, various problems were identified. This paper is intended to assess the implementation of Law No. 11 of 2006 concerning the Government of Aceh. The reason for this is because through the asymmetric decentralization policy, the central government has granted extensive concessions to the Province of Aceh by delegating various administrative and political authorities, managing local identity, to providing financial resources, in accordance with the LoGA. However, the challenge that comes with asymmetric decentralization policy is with the risk of failure in implementation if the central government and the provincial government of Aceh did not implement the mandate of the law optimally.AbstrakPemberian otonomi khusus atau kewenangan khusus oleh pemerintah pusat kepada Provinsi Aceh melalui konsep desentralisasi asimetris bertujuan untuk merangkul provinsi Aceh agar tetap berada dalam kesatuan NKRI dan meningkatkan kesejahteraan masyarakat Aceh. Meski demikian dalam implementasinya ditemukan berbagai permasalahan.Tulisan ini bertujuan untuk melihat bagaimana implementasi Undang-Undang No. 11 Tahun 2006 tentang Pemerintahan Aceh dilaksanakan. Hal ini karena melalui kebijakan desentralisasi asimetris pemerintah pusat telah memberi konsesi-konsesi yang luas kepada Provinsi Aceh dengan melimpahkan berbagai kewenangan administrasi, politik, mengakomodasi identitas lokal, sampai memberikan sumber-sumber keuangan, sebagaimana yang diatur dalam UU PA. Akan tetapi yang menjadi tantangannya adalah, kebijakan desentralisasi asimetris itu bisa terancam gagal apabila dalam pelaksanaannya kinerja pemerintah pusat dan pemerintah provinsi Aceh tidak maksimal dalam melaksanakan amanat UU tersebut.